Análise dos óbitos de causas violentas com toxicológicos positivos para álcool e cocaína em mulheres no Estado do Pará - DINIZ, Laura Andrade (2024)
INTRODUCTION: Currently, drug consumption occurs collectively and excessively, due to the huge amount of substances available on the market and the ease of acquisition, factors that contribute to the dissemination and initiation of consumption. In a general scope, drugs of abuse are classified, according to the legal status of the substances, into licit and illicit. Among licit drugs, the use of alcohol is more predominant in society, with supporters who consume it constantly, which generates alcoholism and various consequences for personal and collective health. The use of licit drugs is a gateway to other types of drug abuse, such as illicit drugs, where the individual associates and enhances the effects on his body. Cocaine is an illegal substance and widely used in association with alcohol, which can result in deaths from intoxication, in addition to being a finding in other types of violent deaths. In this case, the area for obtaining evidence of this associated consumption is forensic toxicology, active in medical expertise centers, where real information on consumption can be obtained through the search for evidence based on different types of techniques. OBJECTIVE: Analyze data from necroscopic examinations of women with positive toxicological results for alcohol and cocaine between the years 2016 and 2022. The deaths analyzed are violent deaths that were autopsied by forensic medicine and examined by forensic toxicology with the specific aim of establishing possible relationships between data such as age, marital status, presence of cocaine in the tests, blood alcohol level and cause of death. METHOD: This is a cross-sectional, descriptive and retrospective epidemiological study that will analyze the incidence of intoxication by alcohol and cocaine in those obtained secondary to non-natural causes, that is, traffic accidents, homicides, suicides, burns and other causes entrusted to the Institute of Legal Medicine and Dentistry, involving female individuals registered with the Scientific Police in the State of Pará between the years 2016 to 2022. Data collection will be monitored in the forensic intelligence sector. From the delivery of the filtered reports via virtual document, the inclusion and exclusion criteria will be assigned by the researchers. The data will be statistically treated appropriately in order to obtain the necessary stratification analyzes showing means and medians, applying the Anova Variance test and post Turkey test, p<0.05.